Penerapan Analisis Klaster dan Prediksi Indeks Pembangunan Manusia untuk Mengevaluasi Kualitas Hidup Manusia dalam Pembangunan Nasional - Ismail, Ghaffar (Seminar Nasional Official Statistics, 2024)
This study evaluates the development of human quality through cluster analysis based on the HDI to achieve the vision of "Golden Indonesia 2045". The purpose of this research is to classify of regencies/cities based on health, education, and standard of living indicators, so that these regions can effectively address their deficient indicators. Using various machine learning methods, AGNES was selected as the best method. The regencies/cities were grouped into four clusters: low, medium, high, and very high. The results show that 244 regencies/cities are in the medium cluster, 188 in the high cluster, 68 in the very high cluster, and 14 in the low cluster. Regencies/cities with low and medium HDI require improvement all aspects, while the high cluster needs to focus on education. Strategic policies in health, education, and decent living standards are essential to enhance quality of life and achieve equitable national development.